1992
DOI: 10.1210/jcem.75.1.1320048
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an age-related decrease in intestinal responsiveness to vitamin D: relationship between serum 1,25-dihydroxyvitamin D3 and intestinal vitamin D receptor concentrations in normal women.

Abstract: Although aged rats reportedly have reduced intestinal vitamin D receptor (VDR) concentrations, it is unclear whether an analogous age-related defect occurs in man. Thus, we assessed the interrelationship among serum 1,25-dihydroxyvitamin D3 [1,25-(OH)2D3], calcium absorption and intestinal VDR in 44 healthy, ambulatory women, ages 20-87 yr. Fractional calcium absorption was measured after oral administration of 45Ca (20 mg CaCl2 as carrier); serum 1,25-(OH)2D3, by the calf thymus binding assay; and serum intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 36 publications
4
44
2
1
Order By: Relevance
“…For this reason no conclusions about pathogenesis of osteoporosis in humans may be drawn. This lack of age-dependent differences is in accordance with findings --gained with identical study design and methodology --in cattle and goat (Riner, 2006;Singer, 2006) and several other reports (Kinyamu et al, 1997;Wood et al, 1998;Lee et al, 2003;Pazianas et al, 2003;Yamagishi et al, 2006) and in contrast to data published elsewhere (Horst et al, 1990;Ebeling et al, 1992;Liang et al, 1994;Bischoff et al, 2001;Duque et al, 2002;Holick, 2003). Since an age and/or estrogen dependent impairment of calcium resorption was detectable in elder subjects in numerous studies, a resistance to vitamin D was postulated (Kinyamu et al, 1997;Wood et al, 1998) and furthermore vitamin D-dependent (Kinyamu et al, 1997;Liel et al, 1999;Schwartz et al, 2000;Leonard et al, 2001;Duque et al, 2002;Gilad et al, 2005) and independent effects of estrogens on calcium resorption were verified (Colin et al, 1999;Eisman, 2001;Van Cromphaut et al, 2003).…”
Section: Resultssupporting
confidence: 90%
“…For this reason no conclusions about pathogenesis of osteoporosis in humans may be drawn. This lack of age-dependent differences is in accordance with findings --gained with identical study design and methodology --in cattle and goat (Riner, 2006;Singer, 2006) and several other reports (Kinyamu et al, 1997;Wood et al, 1998;Lee et al, 2003;Pazianas et al, 2003;Yamagishi et al, 2006) and in contrast to data published elsewhere (Horst et al, 1990;Ebeling et al, 1992;Liang et al, 1994;Bischoff et al, 2001;Duque et al, 2002;Holick, 2003). Since an age and/or estrogen dependent impairment of calcium resorption was detectable in elder subjects in numerous studies, a resistance to vitamin D was postulated (Kinyamu et al, 1997;Wood et al, 1998) and furthermore vitamin D-dependent (Kinyamu et al, 1997;Liel et al, 1999;Schwartz et al, 2000;Leonard et al, 2001;Duque et al, 2002;Gilad et al, 2005) and independent effects of estrogens on calcium resorption were verified (Colin et al, 1999;Eisman, 2001;Van Cromphaut et al, 2003).…”
Section: Resultssupporting
confidence: 90%
“…The inverse relation between the residuals from the regression and age is consistent with the concept of an age-related decrease in intestinal response to calcitriol (Eastell et al, 1991), beginning in the third decade. Studies in normal women have provided evidence for a decrease in intestinal responsiveness to calcitriol with age (Eastell et al, 1991;Ebeling et al, 1992), which may be attributable to a decrease in intestinal vitamin D receptor concentrations (Ebeling et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of crosssectional studies of the effect on age of circulating levels of 1,25D are inconsistent. In women, there are reports that suggest that serum calcitriol increases (Eastell et al, 1991;Ebeling et al, 1992), falls (Gallagher et al, 1979) or does not change (Sherman et al, 1990) with age. Similarly, in men some studies have reported a fall with age (Gallagher et al, 1979;Agnusdei et al, 1998), while in others no change was apparent (Orwoll & Meier, 1986;Sherman et al, 1990;Wishart et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a resistance could be explained by a reduced number of intestinal VDRs (Clemens et al, 1986;Ebeling et al, 1992;Chen et al, 1997), associated with estrogens deficiency, as it was shown after ovariectomy, or by some post-receptorial defects (Parfitt, 1993;Duque et al, 2002). Considered all the above, it can be considered that hypovitaminosis D has multi-factorial origin in elderly.…”
Section: Bone Metabolism During Agingmentioning
confidence: 98%